Evaluation of Information Technology Governance Through The Cobit 5 Framework Approach: Case Study at PT Bank ABC Post-Merger - Yusuf Kurniadi; Desi Adhariani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Governance is the result of accountability for actions taken by the executive board and management to ensure that the processes carried out support the organization's strategic steps towards business goals. As a newly merged company, Bank ABC then rearranged its new vision and mission and adapted it to the dynamics of the organization and stakeholders to support the company's achievements. One of its missions is to provide access to Islamic financial solutions in Indonesia. Providing access to Islamic finance is certainly inseparable from the information technology governance function at Bank ABC. Information technology governance is the embodiment of the structure and roles, processes, and related mechanisms that ensure that information technology is aligned with the organization to achieve organizational goals. For this reason, it is necessary to evaluate good information technology governance to be able to support the achievement of Bank ABC's vision. This study evaluates ABC Bank's information technology governance based on the COBIT 5 framework. Data collection methods in this study used questionnaires and interviews with related parties, especially at the company executive level. Meanwhile, the data analysis technique uses descriptive qualitative which emphasizes the data sources and facts obtained from related parties in the field. The results obtained are expected to result in an evaluation of the extent to which the capability level of information technology governance is, and produce recommendations for improvement so that information technology governance can meet management expectations.